Microstructure of Asphalt Mixtures Using Empty Palm Oil Bunch Waste as Filler Based on Road Engineering Association of Malaysia (Ream) Specifications - Muslika, Muslika; Gusty, Sri; Chaerul, Muhammad (ASTONJADRO, 2025)
Performance of Hollow Asphalt Mixtures Using Empty Palm Oil Bunches Waste Based on Road Engineering Association of Malaysia (Ream) Specifications. One of the road pavement technologies currently being developed is porous asphalt. One of the materials used in flexible pavement mixtures is filler, one of which is ash. stone, which is in limited supply and relatively expensive. One alternative solution is to use empty oil palm fruit bunches. waste as an alternative material in the asphalt mixture. The aim of this research is what is the microstructure of asphalt mixtures that use empty oil palm fruit bunches as filler. This research uses the specifications of the Road Engineering Association of Malaysia (REAM, 2008). From the results of the research carried out, it can be concluded that the use of stone ash filler from empty palm fruit fruit bunches in hollow asphalt mixtures with variations of 2.5%, 5% and 7.5% shows that the granules are dense with voids that cover each other with varying sizes. This is in line with the stability value obtained from the Marshall test. Which has increased due to interlocking of interlocking grains. Meanwhile, from the EDS test results on the composition of chemical elements, it is known that the element contained in the hollow asphalt sample mixed with ash from burning empty oil palm fruit bunches with the highest compound composition is the element Boron at 66.55%, which is different from the chemical composition test for burning ash from bunch waste. The highest compound composition based on atomic percentage is Potassium (K) at 31.6%.